2021
DOI: 10.1519/jpt.0000000000000326
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Supervised Group-Based Otago Exercise Program on Functional Performance in Frail Institutionalized Older Adults: A Multicenter Randomized Controlled Trial

Abstract: Background and Purpose: Because of its high prevalence and association with negative health-related outcomes, frailty is considered one of the most important issues associated with human aging and its mitigation is among the essential public health goals for the 21st century. However, very few studies have focused on institutionalized older adults, despite the knowledge that frailty can be reversible when identified and treated from its earliest stages. Therefore, the objective of this study was to evaluate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 55 publications
(135 reference statements)
1
28
1
Order By: Relevance
“…The postural balance was tested by Berg Balance Scale (BBS) in 4 studies with 263 participants, including 130 in the OEP group and 133 in the control group. [17,20,21,23] The meta-analysis confirmed that BBS scores increased significantly in the OEP group compared to the control group (mean difference [MD] = 5.55; 95% CI = 3.60, 7.50; I 2 = 95%; P < .00001; Fig. 4).…”
Section: Resultsmentioning
confidence: 84%
“…The postural balance was tested by Berg Balance Scale (BBS) in 4 studies with 263 participants, including 130 in the OEP group and 133 in the control group. [17,20,21,23] The meta-analysis confirmed that BBS scores increased significantly in the OEP group compared to the control group (mean difference [MD] = 5.55; 95% CI = 3.60, 7.50; I 2 = 95%; P < .00001; Fig. 4).…”
Section: Resultsmentioning
confidence: 84%
“…The need for four staff members to provide an optimal challenge and engagement of five participants was not sustainable. Maximizing the challenge did not appear to be a priority in recent published studies, which either do not comment on efforts to individualize the intervention [ 21 , 22 ] or allude to progressing the group as a whole [ 23 ]. Chen et al [ 20 ] mention that physiotherapists “guided” participants to modify their exercise level, but the weights used were consistent at 0.5 kg and nurses “led” the intervention, so it is not clear how often physiotherapists may have guided these changes.…”
Section: Discussionmentioning
confidence: 99%
“…This contributed to our increased staff requirements. Existing studies, without commenting on efforts to maximize engagement and challenge of participants, identify beneficial outcomes of group OEP [ 20 , 21 , 22 , 23 ]. In reconsidering the feasibility of group administration of OEP, clear prioritization of safety over maximizing challenge may decrease the need for staff supervision.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations